Doubling as Compositional Axis in Germán Espinosa’s Stories - Sánchez Ávila, Nini Johanna (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The short stories of the writer from Cartagena, Germán Espinosa, are developed under the perspective of Fantastic Literature, which enable a privileged treatment of the structure of ́the double ́. Thus, the analysis proposed in this text considers two particular problems: the first, concerning the determination of the characteristics of the literary double, and the second dealing with the way in which this struc- ture operates as an axis of articulation for most of Germán Espinosa’s narrative work. Due to this, we will introduce four perspectives through which the double or Doppelgänger has been developed in the literary criticism; ranging from Otto Rank ́s psychoanalytical studies (1914), to the mythological criti - cism of Juan Bargelló (1994) and Antonio Ballesteros (1998), from structural perspectives such as that of Lubomír Doležel’s (1995), to a vision of the literary double that considers the concept of illusion (Clément Rosset, 1993). In conclusion, we will analyze a representative sample of Espinosa’s stories in order to examine their interpretative proximities and distances with respect to these theories of literary doubling.